Stability of pelargonidin 3-glucoside in model solutions in the presence and absence of flavanols - Lopes-da-Silva, M.F. (2007)
The stability of pelargonidin 3-g1ucoside (Pg3g1uc), the main anthocyanin in strawberry, has been studied in model citrate solutions (PH 3.5, 25°C) in the absence and presence flavanols (catechin and procyanidin B3) and/or oxygen. Changes in the solutions were monitorized by HPLC-DAD/MS and UV-visible spectra.